A case of undifferentiated pleomorphic sarcoma in esophagus after multiple cancer treatments of surgery and chemoradiotherapy - Yuho Ebata; Yoshihisa Sakaguchi; Yasuo Tsuda; Sho Nambara; Kensuke Kudou; Eiji Kusumoto; Rintaro Yoshida; Tetsuya Kusumoto; Koji Ikejiri (Surgical Case Reports)
Abstract Background Undifferentiated pleomorphic sarcoma (UPS) in the esophagus is extremely rare. Therefore, there are few reports of UPS in the esophagus (UPSE). We present a case of UPSE after multiple cancer treatments. Case presentation A 73-year-old man with a history of cancer treatment, including distal gastrectomy, transverse colectomy, and chemoradiotherapy, was diagnosed with an elevated lesion such as a submucosal tumor in the lower esophagus by regular endoscopy. A boring biopsy was performed, and the specimen showed features of sarcoma. The patient underwent a partial esophagectomy without lymph node dissection. Histopathological findings confirmed an undifferentiated pleomorphic sarcoma. Adjuvant therapy was not administered, and the patient survived without recurrence 1 year after surgery. Conclusions Currently, complete resection is the only treatment option for UPSE. An optimal treatment strategy using chemotherapy or radiotherapy should be established.